On Endogenous Growth with Physical and Human Capital - Caballé, Jordi; Santos, Manuel S. (Journal of Political Economy, 1993)
This paper presents a class of models in which agents may devote part of their nonleisure activities to going to school so as to increase the efficiency units of labor they supply to the firms and the wages they receive. The interaction among the technology of human capital accumulation and agents' preferences will determine endogenously the economy's rate of growth. Given a constant returns to scale technology for physical capital accumulation, we characterize the set of steady states as a ray from the origin and show the global convergence of every off-balanced path to some point on this ray. Further properties concerning the dynamic evolution of the state and control variables around the ray of steady states are also established. Our analysis is useful to understand the role played by the technologies of physical and human capital in the process of accumulation and to evaluate the impact of policies geared toward attaining higher levels of capital. Our results highlight the importance of human capital in the dynamics of growth.